"PER CLERUM ET POPULUM"? LEGAL TERMINOLOGY AND EPISCOPAL APPOINTMENTS IN DENMARK 1059–1225. (29th November 2016) - CIARDI, ANNA MINARA
Abstract : The phrase per clerum et populum ("by clergy and people") was traditionally used to describe how the election of a bishop had been or should be undertaken. Over the course of the twelfth century this changed. Ecclesiastical legislation was step by step revised and codified. The aim of the reformers was to safeguard the autonomy of the Church and to reduce lay influence. The purposes of this article are, first, to examine legal terminology in the context of episcopal appointments from 1059 to 1215, with special reference to the formula per clerum et populum and the role of cathedral chapters as electoral bodies; second, to examine how episcopal appointments were actually undertaken and what terminology was used in the kingdom of Denmark until circa 1225; and, third, to share some ideas about the development of canon law in the context of "cathedral culture." My conclusions are, first, that the mode of election per clerum et populum was gradually replaced and eventually became invalid, parallel to a legal development where cathedral chapters became the "proper" electoral body; second, that the monastic ideals of ecclesiastical freedom prompted by the reformers are evident in normative texts from cathedral chapters in Denmark already in the first quarter of the twelfth century; and, finally, that the legal developments strongly contributed to the formation of capitular institutions and a specific cathedral culture, which was rooted in monasticism but also differed from it, not least with regard to its legal functions.